More new publications from CTA 1 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
More new publications from CTAStrengthening biometry and statistics in agricultural research, Proceedings of a CTA/ University of Hohenheim workshop 1997.ISBN 90 9081 1676, CTA number 850, 20 Credit points.